2003
DOI: 10.1111/j.1440-1584.2003.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Rural General Practitioner Apprehension About Work Related Violence in Australia

Abstract: This study shows that that levels of apprehension about violence affect GPs' willingness to provide after hours services. Future provision of general practice after hours services and home visits in rural areas requires the availability of a safe working environment to reduce GPs' apprehension about workplace violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 3 publications
3
11
0
Order By: Relevance
“…Other characteristics of healthcare workers that have been associated with an increased risk of workplace bullying include gender and marital status. Furthermore, a greater percentage of female physicians fear a potentially violent encounter at work compared to male physicians [93]. Lin and Liu’s study reports that unmarried workers are significantly more likely to experience workplace violence compared to married employees [94].…”
Section: Discussionmentioning
confidence: 99%
“…Other characteristics of healthcare workers that have been associated with an increased risk of workplace bullying include gender and marital status. Furthermore, a greater percentage of female physicians fear a potentially violent encounter at work compared to male physicians [93]. Lin and Liu’s study reports that unmarried workers are significantly more likely to experience workplace violence compared to married employees [94].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, researchers have observed that older workers experience significantly less violence than young workers [100,101]. Other characteristics that have been associated with an increased risk of workplace bullying include gender and marital status; a greater percentage of female physicians, for example, fear a potentially violent encounter at work compared to male physicians [102]. Lin and Liu’s study reports that unmarried workers are significantly more likely to experience workplace violence compared to married employees [103].…”
Section: Discussionmentioning
confidence: 99%
“…Reported prevalence of experienced violence among GPs ranges from 21% to 83% depending on methodology and geographical area studied [34-41]. The apprehension about work-related violence has been found to be particularly high in out-of-hours services [31,42-44]. As most papers on work-related violence in general practice have pointed out, this might have serious consequences for a viable after-hours primary healthcare service.…”
Section: Discussionmentioning
confidence: 99%